Pengaruh Akuntabilitas Publik dan Transparansi Terhadap Kualitas Laporan Keuangan - Arini Kurniawati; Dadang Sadeli (Jurnal Riset Mahasiswa, 2021)
The purpose of this study is to determine the effect of public accountability and transparency on the quality of financial statements in local government. This research was conducted at the Regional Work Unit in Bandung with a total sample of 30 respondents. The method in this research is survey method with descriptive and verification approach. To find out public accountability and transparency on the quality of financial statements in local government used statistical testing. Statistical test used is to use regression, Pearson correlation coefficient, hypothesis test and coefficient of determination. The results of this research also shows that simultaneously public accountability and transparency affect the quality of financial statements of 51.5% while the rest of 48.5% is the influence of other factors outside the three independent variables such as government accounting standards. Good coorperate governance, Internal control system